Synthetic fuels in the German industry sector depending on climate protection level - Hübner, Tobias; von Roon, Serafin (Smart energy (Amsterdam), 2021)
Especially, the electrification of the industry sector is highly complex and challenging, mainly due to process-specific requirements. In this context, there are several industrial processes, where the direct and indirect use of electricity is subject to technical restrictions. In order to achieve the national climate goals, the fossil energy consumption remaining after the implementation of efficiency and sufficiency measures, as well as direct electrification has to be substituted through hydrogen and synthetic gaseous, liquid and solid hydrocarbons. As the main research object, the role of synthetic fuels in industrial transformation paths is investigated and analyzed by combining individual greenhouse gas abatement measures within the Sector Model Industry. Sector Model Industry is an energy consumption model that performs discrete, deterministic energy and emission dynamic calculations with a time horizon up to 2050 at macroeconomic level. The results indicate that the use of synthetic fuels can be expected with a high level of climate protection. The industrial CO2 target in the model makes it necessary to replace CO2 -intensive fossil with renewable fuels. The model uses a total of 163 TWh of synthetic fuels in the climate protection scenario and thus achieves an 88% decrease in CO2 emissions in 2050 compared to 1990. This means that the GHG abatement achieved in industry is within the range of the targeted CO2 mitigation of the overall system in Germany of between 80 and 95% in 2050 compared to 1990. Due to technical restrictions, the model mainly uses synthetic methane instead of hydrogen (134 TWh). The results show that despite high costs, synthetic fuels are crucial for defossilization as a fall back option in the industrial scenario considering high climate ambition. The scenario does not include hydrogen technologies for heat supply. Accordingly, the climate protection scenario uses hydrogen only in the steel industry for the direct reduction of iron (21 TWh). 8 TWh of synthetic oil substitute the same amount of fossil oil in the climate protection scenario. A further analysis conducted on the basis of the model results shows that transformation in the energy system and the use of smart ideas, concepts and technologies are a basic prerequisite for enabling the holistic defossilisation of industry. The findings in the research can contribute to the cost-efficient use of synthetic fuels in industry and thus serve as a basis for political decision making. Moreover, the results may have a practical relevance, not only serving as a solid comparison base for the outcome of other studies, but also as input data for further simulation of energy system transformation paths. [Display omitted]